Factors influencing the adoption of telemedicine health services during COVID-19 pandemic crisis: an integrative research model. Issue 6 (3rd July 2021) - Rahi, Samar; Khan, Mubbsher Munawar; Alghizzawi, Mahmoud
ABSTRACT: This study aims to investigate patient's behaviour towards the adoption of telemedicine health services with the integration of three well-Known theories, namely, unified theory of acceptance and use of technology (UTAUT), the protection motivation theory (PMT) and DeLone & McLean information success model. The results of structural equation modeling indicate that altogether UTAUT, PMT and DeLone & McLean information success model explained 80.4% variance in patient attitude towards adoption of telemedicine health services. Findings suggest that health-care professional can boost patient attitude towards adoption of telemedicine health services by improving factors such as service quality, computer self-efficacy and performance expectancy.